Answer:
(x, y) = (4, -2)
Step-by-step explanation:
The coefficient of y in the second equation is double the coefficient of y in the first. We can subtract twice the first equation from the second to eliminate y.
(3x +4) -2(x +2y) = (4) -2(0)
x = 4 . . . . . . . . . simplify
Substituting into the first equation, we have ...
4 +2y = 0
2 +y = 0 . . . . . . divide by 2
y = -2 . . . . . . . . subtract 2
The solution is (x, y) = (4, -2).
Answer:
Step-by-step explanation:
x = 3
The letter (Z) is the symbol used to represent integers. An integer can be 0, a positive number to infinity, or a negative number to negative infinity.
Answer:
it is 90*
Step-by-step explanation:
PLEASE BRAINLIEST!!!!!!!!
Answer:
try symnolab it helps a lot with math but the answer is 29/1000 0r 0.029
Step-by-step explanation: Hopes this helps :)